The effect of Brexit on the determinants of bank profitability: A case study of commercial banks in Hong Kong Special Administrative Region - Zhong, Yingqi (2019)
This paper is to investigate the determinants of profitability of Hong Kong commercial banks before (2011-2015) and during (2016-2018) Brexit. The Hong Kong banking industry made major adjustments in banking systems and regulations after the financial crisis. Whether the UK's abandonment of its membership of the European Union will affect the Hong Kong economy and its banking industry is a question worth exploring. The bank profitability is measured by return on average assets (ROAA), return on average equity (ROAE) and net interest margin (NIM) as a function of bank-specific and macroeconomic variables. Through the fixed effect model, the empirical result shows that the bank-specific variables, especially cost management, liquidity and credit risk, have a significant influence on bank profitability before and during Brexit, while macroeconomic variables (gross domestic product growth rate and inflation rate) have no significant impact on profitability. The advice that can be drawn from this result is that banks can achieve better profitability mainly by maintaining and improving cost management, increasing liquidity and reduce credit risk. Keywords: Profitability, Determinants, Commercial banks, Hong Kong.